Euthanasia: Is It Morally Justifiable? - Reymand Hutabarat (Fakultas Filsafat Universitas Advent Indonesia, 2013)
The question of euthanasia is one of the most difficult moral problems that arise in the context of terminal medical care. It now occurs with greater frequency and is much more difficult to resolve because of advances in the art and science of medicine. Since the problem of euthanasia is still not clear to many church members in Indonesia, so the purpose of this study is to determine whether the Euthanasia is morally justifiable from the Christian perspective. The result of this study comes into conclusion that euthanasia is a kind of human effort to make a “good or painless death.”Â There are two kind of Euthanasia:Â active and passive. Active Euthanasia is taking human life and passive Euthanasia is simply allowing death to occur in order to avoid suffering. From the point of Christian perspective, active Euthanasia is morally unjustifiable, but passive Euthanasia may be morally justifiable, as long as it is natural and irreversible death. Also, the decision should be taken be consensus of pastor, doctor, lawyer, and family. God should be sought first in prayer and healing. And when the course of death is medically irreversible and no divine inter version is forthcoming, it is morally justified to stop unnatural efforts to prolong the process of dying.